Pendekatan Komunikasi Efektif dalam Pencegahan Perilaku Bullying di Lingkungan Sekolah - Aripin, Nurasma; Pratama, Agus; Sari, Nurhaslita; Sitompul, Siti Jahria; Marlizar, Desi; Sandela, Ilka (Lok Seva: Journal of Contemporary Community Service, 2024)
Effective communication carried out by parents and teachers can be an approach to prevent bullying behavior that occurs in the school environment. Law No. 35 of 2014 concerning Child Protection Article 76 C which states that everyone is prohibited from placed, allowing, doing, instructing or participating in violence against children expressly affirms that bullying behavior experienced by children is protected by law. This awareness underlies this community service activity with socialization methods and discussions on how effective communication can prevent bullying behavior in the school environment. The service activities carried out have the purpose of providing understanding to students and teachers that good communication between students and parents, parents and the school, teachers and students can increase the sense of security and comfort to everyone who is pursuing education. The sense of security and comfort felt by the students will keep them respectful and respectful of each other. The results of PKM activities are expected to make parents, teachers, schools, school committees, and the general public in the future pay more attention to building communication with children or students and schools will always establish partnerships with other schools, the government and other institutions that focus on child development.